The Enron Collapse and Criminal Liabilities of Auditors and Lawyers for Defective Prospectuses in the United States, Australia and Canada: a Review - Solaiman, S.M. (Journal of Law and Commerce, 2008)
A lack of uniformity in laws regulating professionals such as auditors and lawyers in relation to defective prospectuses exists across nations around the world. Securities legislation of some jurisdictions clearly imposes criminal liabilities for defective prospectuses on professionals along with directors and promoters of the issuer of securities. But the laws of some other countries are ambiguous in this regard. Such an ambiguity is present in the securities legislation of the United States, Australia and Canada. Their legislation does not categorically name the persons who should be criminally liable for a defective prospectus; nonetheless auditors and lawyers are sometimes caught by virtue of judicial interpretations of those vague legal provisions. Even though they could be on the hook under such interpretations, legislation provides a wide range of defences that facilitate escaping liabilities by offenders at the expense of the integrity of the market. Regarding sanctions, although the term of imprisonment is identical in all these three jurisdictions, pecuniary penalties significantly vary after the recent reforms triggered by some spectacular corporate bankruptcy taking place especially in the U.S. and Australia. Most importantly, the post-Enron reforms explicitly amend the laws governing secondary securities markets, and therefore their application to defective prospectuses is questionable except for the Canadian reforms. If the post-Enron reforms do not really touch the prospectus liability regimes in the U.S. and Australia, it can be said that the lawmakers have ignored their primary securities markets. If this is so, it would be an unwise policy to wait for an Enron-type disaster to occur in the IPO market for stimulus to initiate reforms addressing professional malpractices in the preparation of prospectuses. If not, the law should make it clear before it is too late.